Determinación del rendimiento potencial de grano del híbrido de Girasol "65A25" utilizando diferentes niveles de fertilización quimica en la zona de Babahoyo - Paredes Lombeida, Sandro Fabricio (2014)
This research was carried out on the grounds of the fifth "Mejía Coca", belonging to Mr. Philadelphus Mejía Coca, located at Km 9.5 of the via Babahoyo - Montalvo; Babahoyo, province of Los Ríos Canton; testing the levels of chemical fertilization 120 - 60-132; 140 70-154; 160 80-176; 180 90-198; 200 100-220; 220 110-242; 240 - 120 - 265 and 0 - 0 - 0 kg / has nitrogen, phosphorus and potassium in hybrid sunflower '65A25', with the aim of: to) determine the potential yield of the hybrid in the climatic conditions of the area of Babahoyo; b) to identify the program of chemical fertilizer to maximize the performance of grain (yield potential) in the hybrid '65A25'; (c) determine the agronomic efficiency of hybrid; and, (d) economic analysis of grain yield based on the production cost of the treatments.